Achievement of age‐friendly health systems committed to care excellence designation in a convenient care health care system. (12th October 2022) - Pohnert, Anne M.; Schiltz, Nicholas K.; Pino, Lilia; Ball, Sarah; Duffy, Evelyn G.; McCormack, Mary E.; Oliver, Brant; Patterson, Angela; Pelton, Leslie; Dolansky, Mary A.
Abstract: Objective: To describe the implementation of the age‐friendly health systems (AFHS) 4Ms Framework, an evidence‐based framework to assess and act on "What Matters, Medication, Mentation and Mobility to deliver Age‐Friendly health care for patients 65 and older", to achieve the Institute for Health care Improvement (IHI) Committed to Care Excellence recognition in a convenient care health system and test two novel implementation strategies. Setting: The study was conducted in over 1100 convenient care clinics in 35 states and DC. MinuteClinics are located in community‐based retail pharmacies in rural, suburban, and urban areas and staffed with approximately 3300 nurse practitioners and physician associates. Design: In Year 1, the project used a quality improvement design, and in Year 2, a quasi‐experimental implementation research design to pilot two strategies at the provider level (Virtual Clinic and Plan‐Do‐Study‐Act (PDSA)). Statistical process control charts were used to assess changes in 4Ms documentation over time. Mixed‐effects Poisson regression was used to assess the effectiveness of the pilot studies. Data Collection: The electronic health record (EHR) was enhanced to capture documentation of the AFHS 4Ms assessments and actions. A learning platform was created to teach and evaluate provider 4Ms competency, and the two data sources were merged into a registry. A formative evaluation was conducted using Tableau and reporting dashboards. Findings: After 18 months and the implementation of 20 strategies to improve the uptake of the 4Ms, MinuteClinic achieved the IHI Committed to Care Excellence recognition. A significant increase over time in the reliable delivery of all 4Ms and each M component individually was found. For the research, there were significant improvements in the mean number of Ms delivered per visit (M‐Score) in the Virtual Clinic (Incident Rate Ratio [IRR]: 2.47, p  = 0.001) and PDSA (IRR: 3.08, p  = 0.002) strategy intervention groups when compared to controls. Conclusions: Application of quality improvement and implementation methodologies contributed to the success of implementing age‐friendly 4Ms evidence‐based practice.